On-demand hydrogen generation by the hydrolysis of ball-milled aluminum composites: A process overview. (19th October 2021) - du Preez, S.P.; Bessarabov, D.G.
Abstract: The hydrolysis of aluminum (Al) is a relatively simple method for on-demand hydrogen generation for niche (low-power, <1 kW) proton exchange membrane fuel cell applications. The hydrolysis of Al in neutral pH water and under standard ambient conditions is prevented by the presence of a thin surficial oxide layer. A promising method to enable Al's spontaneous hydrolysis is by its mechanochemical activation (ball milling) with certain metals (e.g., Bi, Sn, In, Ga). This overview presents several aspects relating to the changes occurring in Al particles during ball milling, e.g., the structural and morphological behavior of Al during ball milling procedures (with and without the presence of activation metals), and the distribution and homogenization of Al and various activation metals. The formation of galvanic cells between anodic Al and cathodic activation metals (relative to Al) is discussed. A summary of the existing Al composites for on-demand hydrogen generation is presented. The paper concludes with a discussion of activation metal recovery, and the effects thereof on the economic feasibility of Al composites for hydrogen generation. Highlights: The use of ball-milled Al for on-demand hydrogen generation is reviewed. The effect of activation metals on Al's structure and reactivity is highlighted. Activation metals (cathode) form galvanic cells with Al (anode). Ternary Al composites showed the most potential for real-world applications. Future research should focus on activation metal recovery and reactor design.